THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON ORGANIZATIONAL TRUST AND JOB SATISFACTION IN VIETNAM - LUONG TAN THINH; NGUYEN DUY THANH (Tạp chí Khoa học xã hội Thành phố Hồ Chí Minh, 2025)
The objective of this study is to examine the impact of Corporate Social Responsibility (CSR) on organizational trust and job satisfaction of employees in enterprises. A total of 233 survey samples were collected from participants in Small and Medium Enterprises (SMEs) in Vietnam. The research data were analyzed using a Structural Equation model (SEM). The research result indicated that the four components of CSR used in this study include economic responsibility, legal responsibility, ethical responsibility, and philanthropic responsibility. The results show that not all CSR components influence organizational trust. Specifically, legal responsibility, ethical responsibility, and philanthropic responsibility have a significant impact on organizational trust. Additionally, organizational trust plays a mediating role in promoting CSR, leading to employee job satisfaction.